(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
Websites are widely used as a means of communication for programs run by a country’s government in this global era. The extinction of languages and various cultures due to the strong current of globalization is inevitable. On the other hand, in this global era, websites could be used as a great dissemination tool for national programs and cultural identity. Like iisma programs from Indonesia that sent their student abroad. Iisma uses websites for spreading information and communicating with their public. This study aims explore how the iisma homepage represents Indonesian national culture. Using visual social semiotic, this study found that the main page of the iisma website represents the dynamic Indonesian culture in the development of Indonesian education on the global stage.